Identifying a Typology of Unlisted Paid Home-Based Child Care Providers Using Latent Profile Analysis. Issue 7 (3rd October 2021) - Hooper, Alison; Slicker, Gerilyn; Riser, Danielle
ABSTRACT: Research Findings: This study provides a framework for categorizing one subset of the large and heterogeneous group of home-based child care providers, unlisted paid providers. We analyzed data on unlisted paid home-based child care providers ( n = 448) from the 2012 National Survey of Early Care and Education conducted in the United States. We used latent profile analysis to explore how providers align into profiles based on key characteristics related to their caregiving beliefs, self-reported instructional practices, professional engagement, and family supportive practices. Findings reveal that unlisted paid home-based providers align into three profiles: Low Instruction, Low Professional Development (51.3%, n = 230); Higher Instruction (35.2%, n = 158); and Engaged with Outside Systems (13.4%, n = 60). Results suggest that there is variation in providers' instructional practices, family supports, and professional engagement activities among profiles. Additionally, provider age, enrollment characteristics, and neighborhood urban density predicted profile membership. Practice or Policy: Results provide insight into the design and implementation of quality improvement supports for this subset of home-based child care providers. Using this typology can help match unlisted paid home-based providers with supports that align with their beliefs and practices. It also adds to the limited research base about this subset of providers that can be used to guide practices and policies related to home-based child care.